Bismuth-catalyzed growth of germanium nanowires in vapor phase - Yan, Chaoyi (2012)
We report the successful synthesis of single crystalline Ge nanowires using Bi as catalyst. To the best of our knowledge, this is the first time Bi was used in vapor phase for Ge nanowire growth. An in situ catalyst evaporation method was used to obtain the high quality Ge nanowires. Diameters of the nanowires are in the range of 10−40 nm and the growth direction is along <111>. Composition analyses showed that the nanowires were composed of Ge while the capping catalyst particles were Bi. Controlled experiments showed that source material with proper Bi/Ge molar ratio was a key aspect for the growth of high purity nanowires. The low-temperature growth of Ge nanowires, enabled by the low eutectic point of Bi/Ge, is especially desired for their potential integration with existing semiconductor technologies.